Hydrogen isotopes (d2H) of polyunsaturated fatty acids track bioconversion by zooplankton - Pilecky, Matthias; Kämmer, Samuel; Mathieu-Resuge, Margaux; Martin-Creuzburg, Dominik; Taipale, Sami; Wassenaar, Leonard; Kainz, Martin (Dryad, 2021)
Organisms at the base of aquatic food webs synthesize essential nutrients,
such as omega-3 polyunsaturated fatty acids (n-3 PUFA), which are
transferred to consumers at higher trophic levels. Many consumers,
requiring n-3 long-chain (LC) PUFA, such as eicosapentaenoic acid (EPA)
and docosahexaenoic acid (DHA), have limited ability to bioconvert them
from the essential dietary precursor α-linolenic acid (ALA) and thus rely
on dietary provision of LC-PUFA. We investigated LC-PUFA metabolism in
freshwater zooplankton using stable hydrogen isotopes (d2H) of fatty acids
as tracers. We conducted feeding experiments with the freshwater keystone
grazer Daphnia to quantify changes in the d2H value of body FA in response
to the FA composition of their food and the d2H value of the ambient
water. The isotopic composition of LC-PUFA changed in Daphnia, depending
on the integration of 2H from ambient water during de novo synthesis or
bioconversion from dietary precursors, allowing us to distinguish dietary
from bioconverted EPA in body tissue. We tested the applicability of these
laboratory findings in a field setting by analyzing d2H values of PUFA in
primary producers and consumers in eutrophic ponds to track EPA sources of
zooplankton. Multilinear regression models that included conversion of ALA
to EPA correlated better with zooplankton d2HEPA than seston d2HEPA at low
dietary EPA supply. This study provides evidence that zooplankton can
compensate for low dietary EPA supply by activating LC-PUFA biosynthesis
and shows that herbivorous zooplankton play a crucial role in upgrading FA
for higher trophic levels during low dietary EPA supply.